Aortic Dissection in Patients With Bicuspid Aortic Valve–Associated Aneurysms - Wojnarski, Charles M. (Ann Thorac Surg, 2015)
BACKGROUND: Data regarding the risk of aortic dissection in patients with bicuspid aortic valve and large ascending aortic diameter are limited, and appropriate timing of prophylactic ascending aortic replacement lacks consensus. Thus our objectives were to determine the risk of aortic dissection based on initial cross-sectional imaging data and clinical variables and to isolate predictors of aortic intervention in those initially prescribed serial surveillance imaging. METHODS: From January 1995 to January 2014, 1,181 patients with bicuspid aortic valve underwent cross-sectional computed tomography (CT) or magnetic resonance imaging (MRI) to ascertain sinus or tubular ascending aortic diameter greater than or equal to 4.7 cm. Random Forest classification was used to identify risk factors for aortic dissection, and among patients undergoing surveillance, time-related analysis was used to identify risk factors for aortic intervention. RESULTS: Prevalence of type A dissection that was detected by imaging or was found at operation or on follow-up was 5.3% (n = 63). Probability of type A dissection increased gradually at a sinus diameter of 5.0 cm—from 4.1% to 13% at 7.2 cm—and then increased steeply at an ascending aortic diameter of 5.3 cm—from 3.8% to 35% at 8.4 cm—corresponding to a cross-sectional area to height ratio of 10 cm(2)/m for sinuses of Valsalva and 13 cm(2)/m for the tubular ascending aorta. Cross-sectional area to height ratio was the best predictor of type A dissection (area under the curve [AUC] = 0.73). CONCLUSIONS: Early prophylactic ascending aortic replacement in patients with bicuspid aortic valve should be considered at high-volume aortic centers to reduce the high risk of preventable type A dissection in those with aortas larger than approximately 5.0 cm or with a cross-sectional area to height ratio greater than approximately 10 cm(2)/m.